Bacteriorhodopsin/phospholipid interactions - a study by ³¹P- and ²H-NMR - Gale, P; Gale, Paul (1988)
﻿ Two methods were used to produce exogenous lipid/bR complexes. A detergent method (Huang et al., 1980) reconstituted bR into DMPC or DMPG bilayers, free of all endogenous purple membrane lipids as shown by high resolution 31 P-NMR. A novel biological detergent-free method employed bovine liver non-specific lipid transfer protein (nsTP) to mediate addition of DMPC to purple membrane, while retaining 76 - 86% of the endogenous purple membrane phospholipids. The variations with temperature of 2H-NMR quadrupole splittings for the DMPC choline α- and β-methylene CD2 segments were similar to those for protein-free lipid (Gaily et al., 1975) implying that temperature dependent changes in segmental amplitudes of motion within the choline group are preserved in the presence of bR. Incorporation of small quantities of bR increased the amplitudes of segmental motion within the choline headgroup relative to that of pure lipid, but increasing the bR content induced an ordering effect. The choline α- and β-methylene segment quadrupole splittings showed a linear variation with protein content at constant temperature. This is consistent with freeze fracture electron microscopy data, which shows the bR particles to be dispersed at all lipid/protein ratios, when quenched from temperatures above the phase transition. Applying a fast two site exchange model to the 2H-NMR data, values between 12 and 15 were calculated for the number of boundary lipids for bR (26,000 Mr) in DMPC bilayers free of purple membrane lipids. From ESR data, for delipidated bR in DMPC and DMPG bilayers at temperatures above the phase transition, the number of boundary lipids calculated were 18 - 21, which is consistent with the bR being monomeric, as also observed in DMPC bilayers with all the purple membrane lipids retained (Cherry et al., 1978). The purple membrane lipids thus appear to mediate crystallization of the bR particles into a hexagonal lattice at temperatures slightly below the exogenous lipid phase transition.